Infective Endocarditis in Pregnancy: A Contemporary Cohort - Countouris, Malamo E.; Marino, Amy L.; Raymond, Megan; Hauspurg, Alisse; Berlacher, Kathryn L. (American Journal of Perinatology, 2022)
Objective Pregnancy-related infective endocarditis (IE) caries a high risk of morbidity and mortality. With increasing intravenous drug abuse (IVDA) amid the opioid epidemic, the risk factor profile may be shifting. In this case series, we aimed to describe risk factors and outcomes for peripartum IE in a contemporary cohort.Study Design We identified patients with IE diagnosed during pregnancy or up to 6 weeks' postpartum from 2015 through 2018 at a single tertiary care center. We abstracted detailed medical history and clinical outcome measures from the electronic medical record. The diagnosis of IE was supported by the modified Duke Criteria.Results Nine patients had peripartum IE: eight (89%) with a history of IVDA, one with an indwelling central venous catheter (11%), and one with prior IE (11%). None had preexisting congenital or valvular heart disease. Six (67%) had comorbid hepatitis C. Eight cases (89%) had gram-positive cocci with vegetations involving the tricuspid valve (56%) and both mitral and tricuspid valves (22%). Major complications included shock (33%), mechanical ventilation (44%), septic emboli (67%), and noncardiac abscesses (33%). Two patients underwent valve surgery, and there were two cases of postpartum maternal mortality (22%), one from septic shock and one from intracerebral hemorrhage. While four patients (44%) delivered preterm (average gestational age 35 weeks), most delivered vaginally (89%) with only one requiring an emergent caesarean section. There was no fetal mortality, although three newborns (43%) required admission to the neonatal intensive care unit. Two patients were initiated on medication-assisted treatment for opioid use disorder. Consultants included infectious disease, cardiology, cardiac surgery, maternal-fetal medicine, and psychiatry.Conclusion These findings confirm that IVDA is a growing risk factor for pregnancy-related IE. Peripartum IE carries a high risk of complications, including maternal mortality, and warrants management with a multidisciplinary care team at a tertiary center.Key Points
Keywords: infective endocarditis; valvular disease; pregnancy; peripartum; intravenous drug use; opioid use disorder